2007
DOI: 10.1007/s10350-006-0812-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischemic Proctitis: Report of Four Cases

Abstract: Acute ischemic proctitis is an extremely rare clinical entity. It is mainly described in patients with significant atherosclerotic and cardiac risk factors who present with lower gastrointestinal symptoms in the setting of hemodynamic instability. Previous reports of ischemic proctitis suggest that rectal resection is not necessary in the treatment of this disease. We present four cases of acute ischemic proctitis that required complete proctectomy. All patients had large vessel atherosclerosis with rectal ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…We do not recommend leaving behind a gangrenous or ischemic segment of the rectum as has been suggested by some 9 . Rather we support the view of Maun et al that leaving behind a gangrenous rectal segment will be a source of persistent sepsis and should be removed 10 . A drain should be left in pelvis and stools be diverted with a colostomy.…”
Section: Discussionsupporting
confidence: 61%
“…We do not recommend leaving behind a gangrenous or ischemic segment of the rectum as has been suggested by some 9 . Rather we support the view of Maun et al that leaving behind a gangrenous rectal segment will be a source of persistent sepsis and should be removed 10 . A drain should be left in pelvis and stools be diverted with a colostomy.…”
Section: Discussionsupporting
confidence: 61%
“…A report by Maun et al [13] disagrees with what Nelson et al have proposed and favors the performance of complete proctectomy in cases of rectal necrosis as retention of dead rectum may add a persistent source of sepsis. The authors describe four cases with acute ischemic proctitis.…”
Section: Discussionmentioning
confidence: 97%
“…In severe cases, a pelvic CT scan may be obtained to rule out pneumatosis and extraluminal air-findings that suggest transmural necrosis and may dictate surgical intervention. 106 Most cases respond to conservative, nonoperative management that includes antibiotics, but severe Anorectal bleeding Daram et al cases requiring complete proctectomy with colostomy have been reported. 103,106 If localized bleeding is noted, endoscopic hemostasis can be attempted with injection therapy, thermal coagulation, or clip application.…”
Section: Ischemic Proctitismentioning
confidence: 97%
“…106 Most cases respond to conservative, nonoperative management that includes antibiotics, but severe Anorectal bleeding Daram et al cases requiring complete proctectomy with colostomy have been reported. 103,106 If localized bleeding is noted, endoscopic hemostasis can be attempted with injection therapy, thermal coagulation, or clip application. In patients with refractory bleeding, angiography with embolization can be successful, but concerns for aggravating the ischemia exist.…”
Section: Ischemic Proctitismentioning
confidence: 97%